Effects of Aromatic Fluorine Substitution on Protonated Neurotransmitters: The Case of 2‐Phenylethylamine. Issue 24 (23rd May 2016) - Schütz, Markus; Bouchet, Aude; Chiavarino, Barbara; Crestoni, Maria Elisa; Fornarini, Simonetta; Dopfer, Otto
Abstract: Fluorination of pharmaceutical compounds is a common tool to modulate their physiochemical properties. We determine the effects of site‐specific aromatic fluorine substitution on the geometric, energetic, vibrational, and electronic properties of the protonated neurotransmitter 2‐phenylethylamine ( x F‐H + PEA, x = ortho, meta, para ) by infrared multiphoton photodissociation (IRMPD) in the fingerprint range (600–1750 cm −1 ) and quantum chemical calculations at the B3LYP‐D3/aug‐cc‐pVTZ level. The IRMPD spectra of all ions are assigned to their folded gauche conformers stabilized by intramolecular NH + ⋅⋅⋅π hydrogen bonds (H‐bonds) between the protonated amino group and the aromatic ring. H→F substitution reduces the symmetry and allows for additional NH + ⋅⋅⋅F interactions in o F‐H + PEA, leading to three distinct gauche conformers. In comparison to o F‐H + PEA, the fluorination effects on the energy landscape (energy ordering and isomerization barriers) in p F‐H + PEA and m F‐H + PEA with one and two gauche conformers are less pronounced. The strengths of the intramolecular NH + ⋅⋅⋅F and NH + ⋅⋅⋅π bonds are analyzed by the noncovalent interaction (NCI) method. Abstract : Fluorination makes the difference : The large effects of site‐specific aromatic fluorination of a protonated prototypical neurotransmitter (2‐phenylethylamine) have been determined by infrared spectroscopy and dispersion‐corrected density functional theory calculations of ions isolated in the gas phase. The strengths of the various competing noncovalent interactions (NH + ⋅⋅⋅π, NH + ⋅⋅⋅F) depend strongly on the fluorination site (see figure).